LATERALISASI SEMIOLOGI BANGKITAN EPILEPTIK PADA EPILEPSI LOBUS TEMPORAL MESIAL DENGAN SKLEROSIS HIPOKAMPUS - Hadet Prisdhiany*, Fitri Octaviana*, Astri Budikayanti*, Joedo Prihartono** (NEURONA, 2015)
INTRODUCTION TEMPORAL LOBE EPILEPSY TLE IS THE MOST COMMON EPILEPSY SYNDROME IN ADULTS IN WHICH TWOTHIRD OF CASES ORIGINATE FROM MESIAL TEMPORAL LOBE MTLE IT ISCAUSED BY HIPPOCAMPAL SCLEROSIS HS AND FREQUENTLYDRUGRESISTANT SEIZURE SEMIOLOGY IS CRUCIAL IN PRESURGICAL EVALUATION TO IDENTIFYTHE EPILEPTOGENIC FOCUS LATERALIZATION